Práctica de la lactancia materna en el puerperio inmediato en un hospital de Norte de Santander (Colombia). - JANITCIS PÉREZ-DURÁN, JANEURIGUI; MARÍA GUIO-MATHEUS, LINA; CONTANZA VERA-ANTOLÍNEZ, ANDREÍNA; LLANOS-REDONDO, ANDRÉS; ALBEIRO ZAMBRANO-MEDINA, NIXON (Salud Uninorte)
Objective: Describe the practice of breastfeeding in the mother-child dyad during the immediate postpartum period in a hospital in Norte de Santander, Colombia. Materials and methods: Quantitative, descriptive, and cross-sectional study, breastfeeding practices were evaluated in the binomials (mother and child), of those in the immediate postpartum period. The first 24 hours after childbirth, the study population is of puerperal women who were hospitalized in the pediatric gynecologist service of a hospital in the North of Santander. Results: Breastfeeding practice, 77 % of nursing mothers adopt appropriate practices, while 23 % show practices considered inappropriate. Conclusions: Younger breastfeeding mothers, first-time mothers, those with a gestational age of less than 37 weeks, and those who had a cesarean delivery are more likely to exhibit inadequate breastfeeding practices.